Institutional changes, money demand, and monetary policy: the case of Saudi Arabia - Al-Badi, Fahad K. A., author; Fan, Liang-Shing, advisor; Kling, Robert W., committee member; Mushinski, David, committee member; Olienyk, John P., committee member (Colorado State University. Libraries, 2002)
The main purpose of this study is to examine the role of institutional developments on the behavior of the demand for money and velocity of money. The ability of policy makers in Saudi Arabia to conduct effective monetary policy has been discussed. This study has investigated the effect of institutional and structural changes on the behavior and stability the demand for money and velocity of money in Saudi Arabia from 1969 to 1999. The study has also surveyed the financial sector's development and structural changes. Further, the functional relationships between the demand for money and the velocity of money and their determinants, including financial institutional development, has been also investigated and tested. The historical review of the developments of the financial system in Saudi Arabia has shown that economic growth has resulted in a rapid expansion of the financial system, thus increasing the demand for more banking services. It has also shown that the Saudi Arabia Monetary Agency (SAMA) has played a major role in the development of the Saudi financial system. The descriptive analysis of the data on real demand for money aim velocity of money in Chapter Five provides strong evidence of a change in the pattern of money supply behavior. The statistical results strongly indicate that the level of income and the degree of financial development determine the real demand for money and velocity of money behavior. The major innovation of the study is the inclusion of the degree of financial development in the examination. The results indicate that significant is played by financial development. The study also shows that the interest rate does not play a significant role. From our discussion in Chapter Four. SAMA plays many roles in Saudi Arabia's financial sector. These roles could have contradictory objectives. An important topic for future research may be "Should SAMA be left to concentrate on sound monetary policy and effective exchange rate policy by giving up other functions?"
Missing page 71.
Keywords: studies; technological change; causality; hypotheses; alliances; variables; copyright; aggregates